The Visual Brain and Peripheral Reading and Writing Disorders : a Guide to Visual System Dysfuntion for Speech-Language Pathologists. - Heeringa, Heidi (SLACK, Incorporated, 2019)
The Visual Brain and Peripheral Reading and Writing Disorders: A Guide to Visual System Dysfunction for Speech-Language Pathologists familiarizes the reader with the complex workings of the human visual system, the motor and sensory components of normal vision as they relate to the recognition of letters and words, and to the acquisition and rehabilitation of reading and writing.